A simple and efficient synthesis of novel aryloxy-functionalised 4, 4'-bi-1, 2, 4-triazoles. (1st May 2016) - Zhang, Li-Juan; Dong, Zhan; Liang, De-Hui; Wang, Zhi-Qiang; Zhao, Ting-Xing; Zhang, Song; Li, Hong-Bo
A simple and efficient strategy for the synthesis of novel aryloxy-functionalised 4, 4'-bi-1, 2, 4-triazoles was successfully explored by nucleophilic aromatic substitution of tetrachloro-4, 4'-bi-1, 2, 4-triazole by various phenols using Cs2CO3 as catalyst. The syntheses were achieved in 25–94% yields.